Analisis Perilaku Konsumen terhadap Keputusan Membeli Produk Tanaman Organik di Kebun Fakultas Pertanian Universitas Nusa Nipa - Elisabeth, Theresia Maria; Noni, Sarlina; Da Rato, Yoseph Yakob (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2021)
Organic agriculture is becoming the newest agricultural sector high Community, and changes in developed and developing countries pay attention to health and the environment. The market of organic farm products is experiencing an increase in the world due to market demand. People today have healthy lifestyle habits that have become a measure of quality. To achieve a balance between busyness and exercise and regularly Eating food can start a healthy life. The further away the food contains chemical drugs or pesticides, the more likely it is to open a beneficial standard of living. This study aimed to analyze the behavior of buyers towards the decision to buy organic plant products in the garden of the Faculty of Agriculture, University of Nusa Nipa Maumere. This research was conducted from 01 October to 01 November 2020. The data collection technique used interviews made observations and filled out a questionnaire prepared by the researcher. Several thirty respondents were interested in data through the purposive sampling technique. The data analysis of this research used the Simple Linear Regression and t-test. The results obtained are the relationship between consumer behavior and the decision to buy an organic plant product has a significant effect, with the strength of the relationship between consumer behavior variables and the decision to purchase organic plant products is very strong and positive, meaning that if consumer behavior is improved, the decision to buy plant products organic also increases